Field study of thermal comfort of the elderly in tree-shaded areas of urban parks in the cold area of China - Zhongjun Zhang; Yaqian Wang; Zhaoji Wu (Scientific Reports)
Abstract Although extreme heat waves present a significant challenge to urban residents, the elderly in China prefer to go outdoors in summer. Shaded areas in parks may offer an ideal space for their outdoor activities. To assess the thermal adaptation of the elderly in open spaces during periods of high temperature, this study conducted an on-site test and survey for two groups, the elderly (aged 60 and above) and the non-elderly (aged below 60), in a park with tree-shaded areas in China. In total, 557 valid samples were collected, including microclimate parameters, visiting patterns, and subjective responses. Statistical analysis showed that the temperature-related parameters in shaded areas were significantly lower than those in open spaces. Among the elderly, 47.5% visited the park daily, and 33.6% chose to go out even when the temperature reached 36.8 ± 2.6 °C. The thermal sensitivity of the elderly was significantly lower than that of the non-elderly. Both groups showed a high level of thermal acceptability at elevated temperatures with no significant difference. For the elderly, the standard effective temperature was 32.4 °C for 80% thermal acceptability, and 25.7 °C for 90% acceptability. The high acceptability might be attributed to psychological adaptation driven by their willingness for outdoor activities.